PENGARUH UKURAN DAN KONSENTRASI PEREKAT TERHADAP SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL LIMBAH ROTAN - Suroto, Suroto (Jurnal Riset Industri Hasil Hutan, 2010)
Shavings rattan waste from the rattan industry can be made into particle board which the addition of glue and hot pressing.  The various of the particle length compositions are, 100% of 1cm of size, mixture of 1cm and 3cm (50%,50%), 1cm and 5 cm (50%, 50%), 3 cm (100%), 3 cm and 5 cm (50%, 50%), and 5 cm (100%). Each of combination was added by 6% and 12% concentration of urea formaldehide glue (UF).  All of the physical and mechanical test results are fulfil the Indonesian Standard of particle board (SNI.03-2105-2006).  Those results are water content 12,36 – 12,49%, thickness increase value 12,25 – 14,15%, density 0,56 – 0,69 g/cm3, hardness 83 – 155 kg/cm2, broken strenght (MOR) 115 – 1306 kg/cm2, bending strenght (MOE) 547 – 6917 kg/cm2,  The best result for Particle  was shown in  and 6% of the glue addition.  The particle boards are classified as medium density board class which has 0,40 – 0,80 g/cm3 of density.  Base on the density chriteria and the glue, the particle board can be use for parts of interior material such as cabinets, desks, bookcase, and etc. Key wood : particle board, rattan waste